Lexical Study Included in the Hidden Comparative Glossary Written by Anselmo Fletes Bolaños: “Lenguaje vulgar, familiar y folklorico de Chile y Nicaragua” (1928) - Martín Cuadrado, Carmen (2024)
This study analyses “Lenguaje vulgar, familiar y folklórico de Chile y Nicaragua” (1928), a hidden comparative glossary published by Anselmo Fletes Bolaños in Revista chilena de Historia y Geografía. Firstly, the context and the biography of the author are presented, followed by a deep comparative study between the variety Chilean and Nicaraguan. Finally, the glossary is valued like a rare comparative material, which doesn’t have normative Spanish as a reference, but it is based on the comparison of two Latin American languages.